Depth of response may predict clinical outcome in patients with recurrent/metastatic head and neck cancer treated with pembrolizumab-containing regimens - Saijo, Ken; Imai, Hiroo; Ouchi, Kota; Sasaki, Keiju; Yoshida, Yuya; Kawamura, Yoshifumi; Taniguchi, Sakura; Kasahara, Yuki; Komine, Keigo; Shirota, Hidekazu; Takahashi, Masanobu; Ishioka, Chikashi (Frontiers in Oncology, 2023)
Background Pembrolizumab-containing regimens are standards of care for recurrent and metastatic head and neck squamous cell carcinoma (R/M HNSCC). The depth of response (DpR) predicts the survival of patients with several types of solid cancers; however, its association with the survival outcomes of patients with R/M HNSCC treated with pembrolizumab-containing regimens remains unclear. Methods This study included 66 patients with R/M HNSCC who received a pemblolizumab-containing regimen as a first-line therapy at Tohoku University Hospital, Sendai, Japan. The patients’ characteristics, combined positive score, baseline tumor size, tumor response, DpR, overall survival (OS), progression-free survival (PFS), PFS2, and adverse events were reviewed. The associations between DpR and survival outcomes were analyzed. Results The 1 year-OS and 1 year-PFS rates of pembrolizumab-containing regimens were 69.4% and 24.4%, respectively. The response rate was 28.8%. The mean and median values of tumor change from baseline were 5.1% and −9.0%. In the correlation analysis, a significant negative correlation was observed between tumor change rate from baseline and survival outcomes (OS: r= −0.41, p=0.0017; PFS: r=−0.49, p<0.001). In the multivariate analysis, DpR with tumor change of ≤−45 was associated with better OS and PFS. Conclusion DpR induced by pembrolizumab-containing regimens may be a predictive factor for OS and PFS in patients with R/M HNSCC.